Assessment of Procedural Distress in Sedated/Intubated Children Under 3 Years Old Using the Newborn Infant Parasympathetic Evaluation: A Diagnostic Accuracy Pilot Study*. Issue 12 (December 2020) - Recher, Morgan; Rousseaux, Jérémie; Flocteil, Mathilde; Jouancastay, Mylène; Potisek, Alice; Lampin, Marie-Emilie; Leteurtre, Stéphane; De jonckheere, Julien
Abstract : Objectives: Newborn infant parasympathetic evaluation index is based on heart rate variability and is related to the autonomic response to pain or stress. The Comfort Behavior Scale is used to assess distress intensity in sedated intubated children. The objective of this study was to assess the validity and performance of newborn infant parasympathetic evaluation as a distress indicator during procedural distress. Design: Monocentric, prospective, noninterventional pilot study of diagnostic accuracy between October 1, 2017, and April 30, 2019. Setting: PICU in a tertiary care university hospital. Patients: Sedated intubated children under 3 years old. Interventions: We continuously obtained mean newborn infant parasympathetic evaluation and instantaneous newborn infant parasympathetic evaluation scores and compared them to Comfort Behavior scores obtained before (T1 period), during (T2 period), and after (T3 period) care procedures. Measurements and Main Results: We obtained 54 measurements from 32 patients. The median age was 4 months (23 d to 31 mo). Between T1 and T2, there was a significant decrease in the instantaneous newborn infant parasympathetic evaluation and mean newborn infant parasympathetic evaluation scores (64 ± 2 to 42 ± 1 [ p < 0.0001] and 64 ± 1 to 59 ± 1 [ p = 0.007], respectively) and a significant increase in the Comfort Behavior scores (from 12 ± 0 to 16 ± 1; p < 0.0001). Comfort Behavior scores and instantaneous newborn infant parasympathetic evaluation and mean newborn infant parasympathetic evaluation scores were significantly inversely correlated ( r = –0.44, p < 0.0001 and r = –0.19, p = 0.01, respectively). With a instantaneous newborn infant parasympathetic evaluation score threshold of 53, the sensitivity, specificity, positive predictive, and negative predictive values to predict a Comfort Behavior Scale up to 17 were 80.0%, 73.5%, 43.8%, and 93.5%, respectively. Conclusions: Instantaneous newborn infant parasympathetic evaluation is valid for assessing distress in sedated/intubated children in the PICU. Further studies are needed to confirm these results and for newborn infant parasympathetic evaluation-based comparisons of sedation-analgesia protocols. Abstract : Supplemental Digital Content is available in the text.